An investigation into the critique that selected independent schools have about the National Curriculum Statement (NCS). - Govender, Thiruvani (My University, 2009)
This research report investigates the critique that selected independent schools have about the new curriculum in South Africa, the National Curriculum Statement (NCS). The NCS was introduced in response to the implementation of a political democratic dispensation in South Africa, in an attempt to marry the philosophy of democracy to education. The NCS is fundamentally different to the apartheid curriculum in that it is based on democratic values that are derived from the South African Constitution. The independent school sector has been vocal in its critique of the NCS. This study thus investigates this critique in an attempt to uncover the reasons that underlie it. Methodologically, this research project is located in the qualitative paradigm. The research participants comprised teachers and heads of curriculum from three schools in the independent sector, as well as managers from the Independent Examinations Board (IEB). The IEB is the assessment body to which the independent school sector belongs. The independent school sector that this study focused on is upper middle class high-fee paying schools, which are located in the ex whites-only suburbs in South Africa. To gather data from the research participants, I used questionnaires and interviews. The combination of structured and unstructured interviews allowed me to systematically probe the research participants’ understandings and views on the NCS. The themes that emerged from the findings are: (1) the old curriculum is used as a benchmark for the NCS; (2) democratic values teaching in the NCS is regarded as optional and (3) educators continue to hold on to their identities in alignment with the past curriculum. One of the key factors that is used to judge the worth of an independent school is the academic results that the school achieves. This has prompted the independent school sector to continue with the same pedagogical practices that they used in the past curriculum, since they have provided the sought-after academic results. In this regard, very little democratic values teaching is taking place in the schools, as intended by the implementation of the NCS. The IEB, as the assessment body, continues to focus on assessment practices that are largely reminiscent of the past curriculum where the main focus was on summative forms of assessment (form of assessment that is used to record a judgement of the performance or competence of a learner), rather than on formative forms of assessment (form of assessment that gives feedback to the learners so that they can improve their performance). This research project concludes with possible suggestions for each group of research participants that could assist them to implement the NCS as it was intended; that is, as a democratic values-based transformational curriculum. Recommendations for future research are also made.
Keywords: Curriculum transformation; Values education; Educator identity; Curriculum critique; Educator autonomy